American Contributions to the 16th International Congress of Slavists, Belgrade, August 2018: Literature - Kornblatt, Judith Deutsch (Book collections on Project MUSE., 2018)
The 2018 volumes of American contributions to the quintennial series of international congresses bringing together the world s Slavists provides a representative sampling of current trends in Slavic literature, linguistics, and philology as practiced in the United States.